2016
DOI: 10.1038/ncomms10822
|View full text |Cite
|
Sign up to set email alerts
|

FAT1 mutations cause a glomerulotubular nephropathy

Abstract: Steroid-resistant nephrotic syndrome (SRNS) causes 15% of chronic kidney disease (CKD). Here we show that recessive mutations in FAT1 cause a distinct renal disease entity in four families with a combination of SRNS, tubular ectasia, haematuria and facultative neurological involvement. Loss of FAT1 results in decreased cell adhesion and migration in fibroblasts and podocytes and the decreased migration is partially reversed by a RAC1/CDC42 activator. Podocyte-specific deletion of Fat1 in mice induces abnormal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
115
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(119 citation statements)
references
References 62 publications
(88 reference statements)
3
115
0
Order By: Relevance
“…Inability to degrade toxic long-chain bases led to decreased viability and slowed growth. Human WT and p.Glu132Gly mutant SGPL1 were found to be able to partially restore dpl1Δ, while p.Arg222Gln, p.Ser346Ile, and p.Tyr416Cys as well as frameshift mutants p.Arg278Glyfs*17 and p.Ser3Lysfs*11 showed no improved growth compared with dpl1Δ ( Figure 2N and Supplemental Figure 7A), consistent with S1P has previously been implicated in the regulation of RHOlike small GTPases (RHOA/RAC1/CDC42), and disruption of RAC1 signaling was previously implicated in the pathogenesis of SRNS (13)(14)(15). We therefore tested whether knockdown of SGPL1 would affect activation of the RHO-like small GTPases.…”
Section: Sgpl1 -/-Mice Exhibit Podocyte Foot Process Effacement Sgpl1supporting
confidence: 61%
“…Inability to degrade toxic long-chain bases led to decreased viability and slowed growth. Human WT and p.Glu132Gly mutant SGPL1 were found to be able to partially restore dpl1Δ, while p.Arg222Gln, p.Ser346Ile, and p.Tyr416Cys as well as frameshift mutants p.Arg278Glyfs*17 and p.Ser3Lysfs*11 showed no improved growth compared with dpl1Δ ( Figure 2N and Supplemental Figure 7A), consistent with S1P has previously been implicated in the regulation of RHOlike small GTPases (RHOA/RAC1/CDC42), and disruption of RAC1 signaling was previously implicated in the pathogenesis of SRNS (13)(14)(15). We therefore tested whether knockdown of SGPL1 would affect activation of the RHO-like small GTPases.…”
Section: Sgpl1 -/-Mice Exhibit Podocyte Foot Process Effacement Sgpl1supporting
confidence: 61%
“…We next examined the effect of AVIL on the PMR, which represents a relevant intermediate cellular phenotype in many forms of monogenic SRNS (8,10,12). We used the IncuCyte ZOOM video microscopy system, which monitors cell migration in real time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, actin remodeling has also been implicated in NS (9). Defects in actin remodeling may be part of the reason why a defect in the podocyte migration rate (PMR) in cell culture has been established as a reliable intermediate phenotype in monogenic forms of SRNS (8,(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…This finding has been accompanied by the discoveries that mutations in human fat1 cause a lethal kidney disease and an increased susceptibility to bipolar disorder [1012], and that FAT1 levels are altered in a wide range of cancers [8,13]. Given that defects in cell motility may underlie many of these conditions, there is growing interest in understanding how these massive proteins affect a cell’s migratory ability.…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, these data suggested that Fat1 plays two roles in epithelial cell migration: polarizing the tissue in the direction of movement, and stimulating the formation of the leading edge protrusions though Ena/VASP-mediated F-actin assembly. Building from this work, Fat1 and Fat2 have since been shown to promote the migration of numerous cell types in vitro [12,14,1620]. …”
Section: Introductionmentioning
confidence: 99%